Implementation of a pilot medical student mentoring program for premedical students and its effects on premedical student attitudes. Issue 3 (2nd July 2020) - Maniam, Ganesh; Dean, Ryan; Urban, Robert S.; Williams, Simon
Abstract: As the medical school admissions process becomes increasingly competitive, there is an increased mental and emotional burden on undergraduate premedical students due to uncertainty about acceptance. Mentors in Medicine is a mentoring program between Texas Tech University Health Sciences Center and Texas Tech University students; the data demonstrate that this program can alleviate some negative emotional aspects faced by premedical students on their journey to medical school. The program interventions include establishing mentor-mentee relationships between medical students and premedical students, hosting various events to encourage dialogue, and promoting communication efforts from medical mentors. These interventions were found to significantly decrease feelings of anxiety or nervousness, as well as feelings of doubt or insecurity. These results may provide a framework for similar medical-premedical mentoring programs at other institutions.